An Overview of Parallel Symmetric Cipher of Messages (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Despite significant developments in communications and technology, data protection has established itself as one of the biggest concerns. The data must be encrypted in order to link securely, quickly through web-based technological data transmission. Transforming plain text into ciphered text that cannot be read or changed by malicious people is the process of encryption.Materials and Methods:In order to maintain the required degree of security, both the cryptanalysis and decryption operations took a significant amount of time. However, in order to cut down on the amount of time required for the encryption and decryption operations to be completed, several researchers implemented the cryptography method in a parallel fashion. The research that has been done on the problem has uncovered several potential answers. Researchers used parallelism to improve the throughput of their algorithms, which allowed them to achieve higher performance levels on the encryption algorithm.Results:Recent research on parallel encryption techniques has shown that graphics processing units (GPUs) perform better than other parallel platforms when comparing their levels of encryption performance.Conclusion:To carry out comparison research on the most significant parallel crypto algorithms in terms of data security efficacy, key length, cost, and speed, among other things. This paper reviews various significant parallel algorithms used for data encryption and decryption in all disciplines. However, other criteria must be considered in order to show the trustworthiness of any encryption. Randomness tests are very important to discover and are highlighted in this study.